2010
DOI: 10.1093/jb/mvq036
|View full text |Cite
|
Sign up to set email alerts
|

Dibutyryl-cAMP up-regulates nur77 expression via histone modification during neurite outgrowth in PC12 cells

Abstract: An elevated level of cyclic AMP (cAMP) within cells activates gene expression through the cAMP-PKA-CREB pathway. Among the CREB target genes, some immediate early genes exist that are responsive to cAMP including the nur77 and c-fos genes. Treatment with dibutyryl-cAMP (dbcAMP) as well as nerve growth factor (NGF) induces neurite outgrowth in PC12 cells. Here, we report that acetylation of histone H3 was gradually stimulated after treatment with dbcAMP in PC12 cells and peaked 1 h after treatment. As the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…24 As Bim is critical for the killing of thymocytes by diverse apoptotic stimuli, 11 we tested whether thymocytes could upregulate Bim in response to catecholamines. Treatment of thymocytes in foetal thymic organ culture (FTOC) with isoproterenol resulted in a robust induction of Nur77, a marker for PKA activation 25 and Bim, whereas the expression of other BH3-only genes, such as Puma (Bbc3) and Noxa remained unchanged (Figure 1c).…”
mentioning
confidence: 99%
“…24 As Bim is critical for the killing of thymocytes by diverse apoptotic stimuli, 11 we tested whether thymocytes could upregulate Bim in response to catecholamines. Treatment of thymocytes in foetal thymic organ culture (FTOC) with isoproterenol resulted in a robust induction of Nur77, a marker for PKA activation 25 and Bim, whereas the expression of other BH3-only genes, such as Puma (Bbc3) and Noxa remained unchanged (Figure 1c).…”
mentioning
confidence: 99%
“…Thus, HDAC inhibitors have been shown to induce specific genes. Previously, we reported the up-regulation of the nur77 gene, followed by histone modification via the protein kinase A signaling pathway or HDAC inhibitor-mediated molecular mechanisms, which in turn extended the neurites of PC12 cells [6,7]. These results emphasized the importance of a control mechanism for neurite outgrowth because this step is involved in the molecular mechanism following cell survival via the transduction of an action potential and release of a neurotransmitter if severe cell damage does not occur [8].…”
mentioning
confidence: 60%
“…We previously reported that PC12 cell treatment with either dbcAMP or NGF induces the expression of the immediate early gene (IEG) nur77 [20]. Since PC12 cells transition from an undifferentiated state to a differentiated state 0-4 h after treatment with K-350, PC12 cells were treated with 5 μM of K-350 for 0, 1, 2, 4 h and changes in nur77 gene expression were analyzed by RT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently demonstrated that Nur77 interacts with Bcl-2, inducing a conformational change in Bcl-2 and converting its function from a cell protective role to a more lethal role [26]. We previously reported that treatment of PC12 cells with dbcAMP induced nur77 gene expression and was associated with acetylation of histone H3 Lys14 [20]. These data suggest that nur77 is localized to the cell nucleus and functions in that compartment to promote neurite outgrowth and in contrast translocates to mitochondria in order to induce apoptosis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation